PENGARUH MODEL JARINGAN TERHADAP KETERAMPILAN BERPIKIR KREATIF PADA SISWA KELAS V SDN KRAMATJEGU 1 - Eka Ratnawati; Neni Mariana; Suryanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The study aims to describe (1) what is a networked model?, (2) what is meant by critical thinking skills?, and (3) determine the influence of the networked model on the creative thinking ability of students in grade V. The method used in this study is an experimental method, which is in the form of a pretest-posttest group where the experiment is only carried out in one group without other comparison groups. An example in this study was thirty elementary school students grade V. Data were collected using literature studies, tests and observations. The study found that (1) the networked model is a learning model that involves children with other learning resources referred to as experts where children have the opportunity to choose learning based on their interests, (2) creative thinking is different from usual which provides unique solutions to problems, (3) there is an influence of network models on the creative thinking skills of students in grade V.